Anti-MAG neuropathy: Role of IgM antibodies, the paranodal junction and juxtaparanodal potassium channels. Issue 10 (October 2018) - Garg, Nidhi; Park, Susanna B.; Howells, James; Noto, Yu-ichi; Vucic, Steve; Yiannikas, Con; Tomlinson, Susan E.; Huynh, William; Simon, Neil G.; Mathey, Emily K.; Spies, Judith; Pollard, John D.; et al.
Highlights: Anti-MAG neuropathy is associated with proximal nerve enlargement. Changes in juxtaparanodal fast potassium channel function may underlie nerve dysfunction. Potassium channels blockers may hence improve nerve function. Abstract: Objective: To improve understanding of disease pathophysiology in anti-myelin-associated glycoprotein (anti-MAG) neuropathy to guide further treatment approaches. Methods: Anti-MAG neuropathy patients underwent clinical assessments, nerve conduction and excitability studies, and ultrasound assessment. Results: Patients demonstrated a distinctive axonal excitability profile characterised by a reduction in superexcitability [MAG: −14.2 ± 1.6% vs healthy controls (HC): −21.8 ± 1.2%; p < 0.01] without alterations in most other excitability parameters. Mathematical modelling of nerve excitability recordings suggested that changes in axonal function could be explained by a 72.5% increase in juxtaparanodal fast potassium channel activation and an accompanying hyperpolarization of resting membrane potential (by 0.3 mV) resulting in a 94.2% reduction in discrepancy between anti-MAG data and the healthy control model. Superexcitability changes correlated strongly with clinical and neurophysiological parameters. Furthermore, structural assessments demonstrated a proximal pattern of nerve enlargement (C6 nerve root cross-sectional area: 15.9 ± 8.1 mm 2 vs HC: 9.1 ± 2.3 mm 2 ; p < 0.05). Conclusions: The imaging and neurophysiological results support the pathogenicity of anti-MAG IgM. Widening between adjacent loops of paranodal myelin due to antibodies would expand the pathway from the node to the juxtaparanode, increasing activation of juxtaparanodal fast potassium channels, thereby impairing saltatory conduction. Significance: Potassium channel blockers may prove beneficial in restoring conduction closer to its normal state and improving nerve function in anti-MAG neuropathy.